TLR2 activation promotes tumour growth and associates with patient survival and chemotherapy response in pancreatic ductal adenocarcinoma - Lundy, Joanne; Gearing, Linden J.; Gao, Hugh; West, Alison C.; McLeod, Louise; Deswaerte, Virginie; Yu, Liang; Porazinski, Sean; Pajic, Marina; Hertzog, Paul J.; Croagh, Daniel; Jenkins, Brendan J. (Oncogene, 2021)
Pancreatic ductal adenocarcinoma (PDAC) has an extremely poor prognosis, and is plagued by a paucity of targeted treatment options and tumour resistance to chemotherapeutics. The causal link between chronic inflammation and PDAC suggests that molecular regulators of the immune system promote disease pathogenesis and/or therapeutic resistance, yet their identity is unclear. Here, we couple endoscopic ultrasound-guided fine-needle aspiration, which captures tumour biopsies from all stages, with whole transcriptome profiling of PDAC patient primary tumours to reveal enrichment of the innate immune Toll-like receptor 2 (TLR2) molecular pathway. Augmented TLR2 expression associated with a 4-gene “TLR2 activation” signature, and was prognostic for survival and predictive for gemcitabine-based chemoresistance. Furthermore, antibody-mediated anti-TLR2 therapy suppressed the growth of human PDAC tumour xenografts, independent of a functional immune system. Our results support TLR2-based therapeutic targeting for precision medicine in PDAC, with further clinical utility that TLR2 activation is prognostic and predictive for chemoresponsiveness.